Study on endophytic bacteria for bioactive compound production use as plant protection agent - RUTH MELLIAWATI; DIAN NOVERITA WIDYANINGRUM; APRIDAH CAMELIA DJOHAN; HARMASTINI SUKIMAN (Society for Indonesian Biodiversity, 2006)
Endophytic microbes are microbes which live symbiotically inside the plant tissue. The potential of those microbes were studied for many purposes such as industrial and agriculture. The purpose of this research was to study the potential of endophytic microbes for bioactive compound production as plants protection agent. From 238 bacteria isolates tested, it were identified that 44 bacteria were against the Xanthomonas campestris, 49 isolates against Pseudomonas solanacearum, 28 isolates against Colletotricum gloeosporioides, 18 isolatesagainst Fusarium oxysporum, 19 isolates against Xanthomonas campestris and Pseudomonas solanacearum, 6 isolates against X. campestris and C. gloeosporioides, four isolates against X. campestris and F. oxysporum, two isolates against P. solanacearum and F. oxysporum, seven isolates against C. gloeosporioides and F. oxysporum, five isolates againt X. campestris, P. solanacearum and C. gloeosporioides. Fermentation process was conducted to collect the bioactive compound against pathogen. Isolates HL.50B.106 couldproduce bioactive compound against C. gloeosporioides, and F. oxysporum, isolates HL.13B.21 against X. campestris and P.solanacearum, isolates Hl.12B.19 against X. campestris, P. solanacearum and C. gloeosporioides. Thin layer chromatography analysis showed specific spot, different from standard (media). Spot was purple in color after sprayed with CeSO4. Rf value of HL.50B.106 extract were 0.51 and 0.53 (fraction 1 and 2), 0.62 and 0.64 (fraction 3 and 4).Â© 2006 Jurusan Biologi FMIPA UNS SurakartaKey words: endophytic bacteria, pathogen microbial against, TLC